The Concept of Knowledge in Islamic Intellectuals - Muhammad Maulidin Baharsyah (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
This article aims to elaborate on the concept of experts and their needs today. This research emphasizes comparative analytical study methods by analyzing problems that exist in the Western world and even among Muslims themselves. The confusion in viewing expert figures as authorities have often given rise to various very complex problems. This stems from the failure to recognize expert figures. The truth is becoming increasingly opaque due to the emergence of various people claiming to be experts, followed by the proliferation of information. It is hoped that the birth of a healthy science culture will be able to overcome such problems. So that complete recognition of experts can occur. Thus, this research aims to restore the expert’s position as an authoritative expert, of course, following his capacity and abilities.